Multimodal Perioperative Ultrasound Course for Interns Allows for Enhanced Acquisition and Retention of Skills and Knowledge. Issue 7 (1st October 2015) - Mitchell, John D.; Montealegre-Gallegos, Mario; Mahmood, Feroze; Owais, Khurram; Wong, Vanessa; Ferla, Brian; Chowdhury, Seema; Nachshon, Akiva; Doshi, Rajiv; Matyal, Robina
<x xml:space="preserve">Abstract</x> The ability to apply perioperative ultrasound techniques is a desirable skill for clinicians. We implemented a multimodal 13-day basic ultrasound course for 6 anesthesia interns. Their scores on a knowledge test increased after the course and were sustained and similar to those of 6 senior residents 90 days later. The interns acquired images of the heart in volunteers with little assistance after the course. They maintained their ability to acquire echocardiographic images on a simulator 90 days later with kinematic measures superior to the same seniors. Through this course, interns gained knowledge and skills equal to or greater than seniors.